An Analysis of Speech Acts in Think Globally Act Locally Textbook For 9th Grade Studentsa - Hafidzhatu Zhahira Syahwa; Elisa Nurul Laili (LPPM Universitas PGRI Semarang, 2026)
This research is motivated by the importance of pragmatic competence in English language learning at the junior high school level, where students often master grammatical structures but struggle to interact naturally in real-life situations. There is a noticeable gap in textbooks which frequently emphasize linguistic aspects over sociopragmatic dimensions. The purpose of this study is to identify the types of speech acts, describe their realization across various text types, and examine their potential in supporting students' pragmatic competence within the 9th-grade English textbook